Low respiratory quotient correlates with high mortality in patients undergoing mechanical ventilation - Shinozaki, Koichiro; Yu, Pey-Jen; Zhou, Qiuping; Cassiere, Hugh A.; John, Stanley; Rolston, Daniel M.; Garg, Nidhi; Li, Timmy; Johnson, Jennifer; Saeki, Kota; Goto, Taiki; Okuma, Yu; et al. (The American journal of emergency medicine, 2024)
Oxygen consumption (VO2), carbon dioxide generation (VCO2), and respiratory quotient (RQ), which is the ratio of VO2 to VCO2, are critical indicators of human metabolism. To seek a link between the patient's metabolism and pathophysiology of critical illness, we investigated the correlation of these values with mortality in critical care patients. This was a prospective, observational study conducted at a suburban, quaternary care teaching hospital. Age 18 years or older healthy volunteers and patients who underwent mechanical ventilation were enrolled. A high-fidelity automation device, which accuracy is equivalent to the gold standard Douglas Bag technique, was used to measure VO2, VCO2, and RQ at a wide range of fraction of inspired oxygen (FIO2). We included a total of 21 subjects including 8 post-cardiothoracic surgery patients, 7 intensive care patients, 3 patients from the emergency room, and 3 healthy volunteers. This study included 10 critical care patients, whose metabolic measurements were performed in the ER and ICU, and 6 died. VO2, VCO2, and RQ of survivors were 282 +/− 95 mL/min, 202 +/− 81 mL/min, and 0.70 +/− 0.10, and those of non-survivors were 240 +/− 87 mL/min, 140 +/− 66 mL/min, and 0.57 +/− 0.08 (p = 0.34, p = 0.10, and p < 0.01), respectively. The difference of RQ was statistically significant (p < 0.01) and it remained significant when the subjects with FIO2 < 0.5 were excluded (p < 0.05). Low RQ correlated with high mortality, which may potentially indicate a decompensation of the oxygen metabolism in critically ill patients.